A multi-sensor approach to automatically recognize breaks and work activities of knowledge workers in academia - Di Lascio, Elena; Gashi, Shkurta; Hidalgo, Juan Sebastian; Nale, Beatrice; Debus, Maike; Santini, Silvia (Proceedings of the ACM on Interactive, Mobile, Wearable and Ubiquitous Technologies, 2020)
Personal informatics systems for the work environment can help improving workers' well-being and productivity. Using both self-reported data logged manually by the users and information automatically inferred from sensor measurements, such systems may track users' activities at work and help them reflect on their work habits through insightful data visualizations. They can further support interventions like, e.g., blocking distractions during work activities or suggest the user to take a break. The ability to automatically recognize when the user is engaged in a work activity or taking a break is thus a fundamental primitive such systems need to implement. In this paper, we explore the use of data collected from personal devices – smartwatches, laptops, and smartphones – to automatically recognize when users are working or taking breaks. We collect a data set of of continuous streams of sensor data captured from personal devices along with labels indicating whether a user is working or taking a break. We use multiple instruments to facilitate the collection of users' self-reported labels and discuss our experience with this approach. We analyse the available data – 449 labelled activities of nine knowledge workers collected during a typical work week – using machine learning techniques and show that user-independent models can achieve a (F1 score) of 94% for the identification of work activities and of 69% for breaks, outperforming baseline methods by 5-10 and 12-54 percentage points, respectivel
Keywords: Multi-modal sensing; human activity recognition; knowledge workers

Arbeitsplatzunsicherheit: Persönliche und kulturelle Faktoren gewichten stark [Job insecurity: Personality-related and cultural factors have a strong impact] - Debus, Maike (2011)

Arbeitsplatzunsicherheit und organisationale Kommunikation [Job insecurity and organizational communication] - Debus, Maike (Interne Kommunikation [Internal communication], 2019)

A story of gains and losses: intra-individual shifts in job characteristics and well-being when transitioning to a managerial role - Debus, Maike E.; Fritz, Charlotte; Philipp, Michel (Journal of Business and Psychology, 2019)
Building on conservation of resources theory, we examined the duality inherent in one of the most significant work-related transitions an employee may go through: becoming a manager. Specifically, we explored intra-individual resource gains (i.e., increases in participation in decision-making) and resource losses (i.e., increases in time pressure) and their associations with intra-individual shifts in well-being (i.e., job satisfaction, exhaustion, and work-to-family conflict) when employees transitioned to a managerial position. In addition, we examined whether new managers’ perceived ability to detach from work during nonwork time moderated these processes. Multilevel analyses among 2052 individuals demonstrated that individuals experienced both a resource gain and a loss when they became managers. As expected, there was an indirect effect of the transition to a managerial position to an increase in job satisfaction via an increase in participation in decision-making. Additionally, there were indirect effects of the transition to a managerial position to an increase in both exhaustion and work-to-family conflict via an increase in time pressure. In line with the hypotheses, we found that new managers who perceived that they were able to detach well experienced a weaker increase in exhaustion and work-to-family conflict (as transmitted via an increase in time pressure). Contrary to the hypothesis, perceived ability to detach reduced the increase in job satisfaction (as transmitted via an increase in participation in decision-making). Our findings shed light on the intra-individual processes that occur when employees become managers, indicating that this transition can be a “double-edged sword.”.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Exhaustion; Manager; Psychological detachment; Well-being

Being tough versus tender: The impact of country-level and individual masculinity orientations as moderators of the relationship between job insecurity and job attitudes - Debus, Maike E.; Kleinmann, Martin; König, Cornelius J.; Winkler, Silvan (Applied Psychology, 2020)
Having a job constitutes one of the most potent means of attaining ‘masculine’ goals such as status, success, and material rewards. In the present research, we examine whether masculinity, both as a country-level value and an individual orientation, moderates the relationship between job insecurity and job attitudes. In Study 1, we draw on cross-cultural data of 20,988 employees from 17 countries. We find that job insecure individuals from countries with higher masculinity values show stronger decrements in job satisfaction (but not commitment). Shedding light on the underlying mechanism, we show that the moderating effect of masculinity is transmitted through two social job characteristics, perceived supervisor interpersonal justice and coworker support. We then constructively replicate the moderating effect of masculinity in Study 2. In a one-country sample of 319 employees, individual masculinity orientations likewise strengthen the negative relationship between job insecurity and job satisfaction. Our research highlights that country-level and individual masculinity orientations yield comparable effects in the job insecurity appraisal process, and provides insight into how cultural values can be enacted at the individual level.
CRIS-Team Scopus Importer:2020-04-02

Bericht über den 16. Kongress der European Association of Work and Organizational Psychology (EAWOP) und die 8. Tagung der Fachgruppe Arbeits-, Organisations- und Wirtschaftspsychologie in der Deutschen Gesellschaft für Psychologie in Münster, 22.-25. 05. 2013 - Debus, Maike (Zeitschrift für Arbeits- und Organisationspsychologie, 2014)

Catch me if I fall! Enacted uncertainty avoidance and the social safety net as country-level moderators in the job insecurity-job attitudes link - Debus, Maike E.; Probst, Tahira M.; König, Cornelius J.; Kleinmann, Martin (Journal of Applied Psychology, 2012)
Job insecurity is related to many detrimental outcomes, with reduced job satisfaction and affective organizational commitment being the 2 most prominent reactions. Yet, effect sizes vary greatly, suggesting the presence of moderator variables. On the basis of Lazarus's cognitive appraisal theory, we assumed that country-level enacted uncertainty avoidance and a country's social safety net would affect an individual's appraisal of job insecurity. More specifically, we hypothesized that these 2 country-level variables would buffer the negative relationships between job insecurity and the 2 aforementioned job attitudes. Combining 3 different data sources, we tested the hypotheses in a sample of 15,200 employees from 24 countries by applying multilevel modeling. The results confirmed the hypotheses that both enacted uncertainty avoidance and the social safety net act as cross-level buffer variables. Furthermore, our data revealed that the 2 cross-level interactions share variance in explaining the 2 job attitudes. Our study responds to calls to look at stress processes from a multilevel perspective and highlights the potential importance of governmental regulation when it comes to individual stress processes.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Cross-cultural; Enacted uncertainty avoidance; Job insecurity; Social safety net; Stress

Der organisationale Wiedereinstieg von Müttern: Hürden und erleichternde Faktoren - Debus, Maike; Palffy, Patricia; Philipp, Stefanie (2019)

Examining occupational self-efficacy, work locus of control and communication as moderators of the job insecurity-job performance relationship - Koenig, Cornelius J.; Debus, Maike E.; Haeusler, Stephanie; Lendenmann, Nora; Kleinmann, Martin (Economic and Industrial Democracy, 2010)
Employees’ performance has been shown to be moderately hampered by job insecurity. Based on conservation of resources theory, the study examines whether three possible resources (occupational self-efficacy, work locus of control and communication) moderate the negative job insecurity—performance relationship. Analyses of a large Swiss dataset reveal two significant interaction effects: the higher the job insecurity, the less influence work locus of control and perceived communication exert on the job insecurity—performance relationship. This suggests that work locus of control and perceived communication may be resources that can only act beneficially in a situation of low job insecurit
CRIS-Team Scopus Importer:2020-04-02
Keywords: Buffer variable; Conservation of resources theory; In-role behaviour; Job security; Organizational citizenship behaviour

Examining the effects of negative affectivity on self- and supervisor ratings of job stressors: the role of stressor observability - Debus, Maike E.; Koenig, Cornelius J.; Kleinmann, Martin; Werner, Christina S. (Work and Stress, 2015)
In this study, we investigated job stressor ratings through Lazarus' transactional stress theory and the usefulness of supervisor ratings as an alternative to employee self-reports. Based on the finding that negative affectivity (NA) causes incumbents to over-report job stressors, we hypothesized that supervisors may also be affected by their NA when appraising an incumbent's job stressors. Building upon the literatures on judgement processes and social-cognitive information processing, we further hypothesized that stressor observability is an important boundary condition. Specifically, we hypothesized that the impact of NA on both self- and supervisor-reported job stressors should increase as stressor observability decreases. Moreover, we hypothesized that incumbent and supervisor ratings would converge less as stressor observability decreases. Data from 260 incumbent-supervisor dyads showed that stressor observability reduced the impact of supervisor NA on supervisor ratings (but not the impact of incumbent NA on incumbent stressor ratings). Further, as hypothesized, incumbent and supervisor ratings showed less convergence the less observable the stressor was. The results highlight the importance of personal and situational factors in the stressor appraisal process – an issue that advances both research and practice in the field of stressor ratings.
CRIS-Team Scopus Importer:2020-04-02
Keywords: appraisals; job incumbent ratings; Job stressors; negative affectivity; observability; supervisor ratings

Flow erleben und Flow erforschen [Experiencing and researching flow] - Debus, Maike; Henk, Florian; Deutsch, Werner; Thoma, Esther; Schulz, Nina (Pauken mit Trompeten. Lassen sich Lernstrategien, Lernmotivation und soziale Kompetenzen durch Musikunterricht fördern?, 2009)

Go with the flow, but keep it stable? The role of flow variability in the context of daily flow experiences and daily creative performance’ - Stollberger, Jakob; Debus, Maike E. (Work and Stress, 2020)
This study investigates the correlates of daily flow experiences at work as well as flow variability (i.e. a person's level of variability in daily flow states) on daily levels of creative performance. Drawing from broaden and build theory, we hypothesised that higher levels of daily flow would be positively related to higher levels of daily creative performance. Extending research on within-person variability of flow experiences, we introduced the concept of flow variability; in particular, we hypothesised that flow variability would be negatively related to a person's creative performance at the day-level. In contrast, based on the notion of heightened reactivity in the context of intra-individual variability, we predicted that the relationship between daily flow and daily creative performance would be stronger among persons with high flow variability. We collected diary data from 44 full-time employees, who provided information on a total of 201 days. Results of multilevel analyses confirmed our predictions. Our study highlights the benefits of examining the different correlates of flow variability across levels, thus revealing an intricate web of cross-level linkages between daily flow states, flow variability, and daily creative performance at work.
CRIS-Team Scopus Importer:2020-04-02
Keywords: creative performance; diary study; Flow experiences; flow variability

I am nice and capable! How and when newcomers’ self-presentation to their supervisors affects socialization outcomes - Gross, Christian; Debus, Maike; Liu, Yihao; Wang, Mo; Kleinmann, Martin (Journal of Applied Psychology, 2020)
Whereas meta-analytical research draws a relatively unfavorable picture of the usefulness of self-presentation on the job, our study challenges this view by highlighting the benefits of such behaviors during newcomer socialization. Drawing from social influence theory, the current study examines how and when newcomers’ self-presentation, in the form of ingratiation and self-promotion, facilitates their socialization success (indicated by affective commitment, job performance, and promotability) by shaping their supervisors’ relational and work-based socialization efforts. Data from a time-lagged field study of 355 newcomer-supervisor dyads provided support for the proposed model. In particular, we found that ingratiation was positively related to supervisor relational socialization effort, which in turn was positively related to newcomer affective commitment. Additionally, self-promotion was positively related to supervisor work-based socialization effort, which in turn was positively related to newcomer job performance and promotability. Drawing on social influence theory’s notion that characteristics related to the influencer may further affect self-presentation effectiveness, we found that newcomers’ interpersonal influence and work role clarity weakened the positive effects of newcomer self-presentation on supervisor socialization efforts. These findings illustrate how newcomers can achieve desirable socialization outcomes by enacting social influence on organizational insiders with self-presentation, extending the literatures on both self-presentation and newcomer socializatio

Insecure about how to rate your job insecurity? A two-study investigation into time frames applied to job insecurity measures - Debus, Maike; Greulich, Berit; Kleinmann, Martin; König, Cornelius J. (Occupational Health Science, 2019)
Job insecurity is typically assessed via self-reports, with items usually being generic and non-contextualized (e.g., “I am sure I can keep my job”). Yet, such items may leave substantial room for interpretation, thus potentially individually biasing construct measurement. To test this, we added a time marker as a frame of reference to job insecurity items in Study 1. In a between-subjects design, participants completed a job insecurity measure under three conditions: near future-focused (i.e., job insecurity was rated with regards to the next sixth months), far future-focused (i.e., next five years), and unframed (i.e., no time reference). In the unframed condition we also asked participants which time frame they had in mind while completing the survey. Results showed that individuals’ job insecurity increased with longer time frames. In Study 2, we assessed common correlates of job insecurity and asked individuals about the time frame they had in mind when thinking about job insecurity as well as their reasons for this choice. Employees who chose longer time frames reported higher commitment, lower turnover intentions, lower psychological health complaints, and higher tenure. Qualitatively analyzing respondents’ reasons for selecting a particular time frame indicated that they either referred to time frames that were determined by their organization or politics, time frames that were determined by their position, individually predictable time frames, or individual time frames regarding professional development. Thus, giving items a frame can impact people’s stressor ratings, which implies that future job insecurity research should employ clear time frames
Keywords: frame of reference; contextualization; job insecurity; stressor perception

Job insecurity and performance over time: the critical role of job insecurity duration - Debus, Maike E.; Unger, Dana; König, Cornelius J. (Career Development International, 2019)
Research on the relationship between job insecurity and job performance has thus far yielded inconclusive results. The purpose of this conceptual paper is to offer a more dynamic perspective on the effects of job insecurity on job performance. Approach. Drawing from cognitive appraisal theory, research on critical life events and stress reactions as well as more general theorizing around the role of time, this paper proposes that individuals’ job performance reactions to job insecurity will be dynamic over time. Findings. Adopting a person-centered perspective, this paper suggests that there are seven subpopulations that differ in their intra-individual job performance change patterns over time. Research implications. This paper presents potential predictors of subpopulation membership and presents an agenda for future research. Originality/value. This conceptual paper contributes to the literature by introducing a dynamic perspective to the study of job performance in the context of job insecurity. Delineating a set of open questions that follow from the presented theoretical arguments, the authors also hope to stimulate future research in the context of job insecurity and job performanc
CRIS-Team Scopus Importer:2020-04-02
Keywords: Duration; Job insecurity; Job performance; Longitudinal

Making flow happen: The effects of being recovered on work-related flow between and within days - Debus, Maike E.; Sonnentag, Sabine; Deutsch, Werner; Nussbeck, Fridtjof W. (Journal of Applied Psychology, 2014)
This article examines variations of work-related flow both between and within days. On the basis of the effort-recovery model (Meijman & Mulder, 1998), we hypothesized that a person's relative day-specific state of being recovered (i.e., feeling refreshed) in the morning is positively related to subsequent day-level flow experiences during work. Taking into account research on circadian rhythms of human functioning, we further hypothesized that flow experiences follow a U-shaped pattern within the working day and that feeling recovered will affect this pattern. One hundred and twenty-one software professionals provided data on recovery at the start of the working day and on flow at 3 occasions during the day, for a period of 5 consecutive working days (resulting in 493 day-level and 1,340 occasion-level data points). Three-level multilevel models showed that relative day-level state of being recovered predicted day-level flow experiences in the hypothesized direction. The data did not support a general curvilinear, U-shaped main effect of flow experiences within the day. However, people in a relatively high state of being recovered in the morning experienced the predicted U-shaped pattern, whereas poorly recovered people experienced a gradual decrease in flow experiences over the course of the working day. This study emphasizes the importance of recovery during nonwork time for flow experiences within the entire working day, thereby extending research on task characteristics with personal resources when examining predictors of flow.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Curvilinear effects; Experience sampling study; Flow experiences; Recovery

Onboarding - Wie der Stellenantritt gelingt [Onboarding – How organizational socialization works out] - Debus, Maike (2013)

Perceived overqualification and collectivism orientation: Implications for work and non-work outcomes - Luksyte, Aleksandra; Bauer, Talya; Debus, Maike; Erdogan, Berrin; Wu, Chia-Huei (Journal of Management, 2020)
In this research, we simultaneously examined the relative applicability of person-environment fit and relative deprivation theories in explaining the interactive effects of perceived overqualification and collectivism cultural orientations on positive outcomes. We hypothesized that the negative (positive) influence of perceived overqualification on person-environment fit (relative deprivation) will be weaker among employees with high collectivism cultural orientation. We also examined which of these two different mechanisms would explain the hypothesized interactive effects in predicting these workers’ citizenship behavior, personal initiative, work engagement, and life satisfaction. We tested our hypotheses in two studies. In Study 1, we recruited professional staff (n = 852) and their coworkers (n = 301) from 95 universities and tested our hypotheses in a matched sample of 190 employees and their peers. The moderated mediation results supported the idea of person-environment fit (but not relative deprivation) as the mechanism explaining why collectivism orientations assuaged the negative effects of perceived overqualification on these outcomes. We constructively replicated these results in Study 2, which was a time-lagged design with full-time employees (n = 224). Study 2’s results further supported the robustness of our model by testing alternative moderators, mediators, and outcomes.<br

Response behavior in work stress surveys: A qualitative study on motivational and cognitive processes in self- and other-reports - Greulich, Berit; Debus, Maike; Kleinmann, Martin; König, Cornelius J. (European Journal of Work and Organizational Psychology, 2020)
Work stressors have major consequences for employees’ health and performance, and it is thus in the interest of organizations to assess them. Although organizations often ask employees to fill out work stress surveys regarding stressors and resources, the literature on survey responding offers only limited advice on how to formulate work stress surveys. Furthermore, self-, supervisor-, and coworker-reports show only low convergence. To deepen our understanding of motivational and cognitive processes when individuals respond to work stress surveys, we used a qualitative, grounded theory approach. We interviewed employees after they responded to representative items, asking them about their thoughts, motivational processes, potential factors that might have biased their responses, and the contexts they considered when responding. Since organizations are often also interested in other-reports of stress at work, we also interviewed supervisors and coworkers.We reached theoretical saturation after 31 interviews. A multi-stage coding-process with three raters resulted in new theoretical findings regarding motivational processes, comparisons, and differences between self- and other-reports. For example, employees sometimes deliberately distort answers for fear of consequences. Furthermore, employees, supervisors, and coworkers undergo different comparison processes. The findings of this study suggest that more specific and context-rich wording of items may lead to a more reliable and comparable assessment of stressors and resources at work.<br

The building blocks of job insecurity: The impact of environmental and person-related variables on job insecurity perceptions - Debus, Maike E.; Koenig, Cornelius J.; Kleinmann, Martin (Journal of Occupational and Organizational Psychology, 2014)
This study unites two perspectives concerning the determinants of job insecurity perceptions that exist in the literature and that resemble the classical nature–nurture debate. On the ‘nurture’ side, we investigated the company performance and type of contract, while we focused on negative affectivity and locus of control on the ‘nature’ side. In addition to demonstrating the known main effects of the respective predictors, we examined the proportional reduction in prediction error for both predictor types. Based on Lazarus’ stress model, we also hypothesized interactive effects between the environmental and person-related predictors. Multilevel analyses of 640 employees from 50 companies revealed that all four variables significantly and incrementally predicted job insecurity in the hypothesized direction. Interestingly, the person-related variables contributed more than twice as much to the reduction in prediction error in job insecurity perceptions when compared with the environmental variables. Among the hypothesized interaction effects, only locus of control significantly interacted with type of contract in predicting job insecurity perceptions (employees on a temporary contract experienced a steeper incline in job insecurity perceptions with increasing levels of external locus of control relative to employees on a permanent contract). We discuss implications for the conceptualization of job insecurity as well as practical implication
CRIS-Team Scopus Importer:2020-04-02

The interactive effects of dual-earner couples’ job insecurity: Linking conservation of resources theory with crossover research - Debus, Maike E.; Unger, Dana (Journal of Occupational and Organizational Psychology, 2017)
The present study examines job insecurity in the context of dual-earner couples. Linking conservation of resources theory (e.g., Hobfoll, 1989, Am. Psychol., 44, 513) with crossover research (e.g., Westman, 2001, Hum. Relat., 54, 717), we proposed that a partner's job insecurity constitutes an additional resource threat. Thus, the partner's job insecurity would exacerbate a person's negative reaction to his or her own job insecurity in terms of attitudinal (i.e., work engagement) and both health- and withdrawal-related outcomes (i.e., psychological health and turnover intention). Using a time-lagged design and multisource data from 171 mixed-gender dual-earner couples, multilevel path analysis applying the Actor-Partner-Interdependence Model revealed interesting gender differences. The negative relationship between the husband's job insecurity and his work engagement was stronger, the higher his wife's job insecurity was. The data further showed a moderated mediation, such that the husband's job insecurity was negatively and indirectly related to both psychological health and turnover intention (via reduced work engagement) if his wife experienced a medium or high level of job insecurity. Our study demonstrates the interactive effects of stressors in dual-earner couples, and highlights the importance of overcoming an overly individualistic perspective when studying job insecurity in particular and stressors more generall
CRIS-Team Scopus Importer:2020-04-02
Keywords: dual-earner couples; health; job insecurity; stress; work engagement

The power of doing: How job crafting transmits the beneficial impact of autonomy among overqualified employees - Debus, Maike E.; Gross, Christian; Kleinmann, Martin (Journal of Business and Psychology, 2020)
Overqualified individuals have more experience, KSAs (knowledge, skills, abilities), and/or education than what is needed in their job. Prior research has identified autonomy as a work characteristic that helps individuals deal with overqualification; yet, it remains unclear as to why this is the case. The goal of the present study was to identify the mechanism through which autonomy exerts its beneficial impact. Drawing on the literatures of person-environment fit and proactivity, we first hypothesized that, in addition to autonomy, job crafting likewise moderates the relationship between overqualification and both withdrawal and turnover intention as central outcomes. Job crafting denotes a proactive type of behavior whereby individuals change the boundaries of their jobs. Next, we hypothesized that job crafting is positively related to autonomy, and that job crafting represents the key mechanism through which autonomy moderates the overqualification-outcome relationship. In a multisource sample of 226 employee-supervisor dyads, we found that overqualified employees were significantly more likely to withdraw from their work and intend to exit if (a) their job provided little autonomy or (b) if they engaged in low levels of job crafting. When individuals experienced high levels of autonomy or engaged in high levels of job crafting, the overqualification-outcome relationship was reversed (or non-significant). Moreover, autonomy was positively related to job crafting. Finally, we found evidence for mediated moderation, such that the moderating effect of autonomy on the relationship between overqualification and both withdrawal and turnover intention was transmitted through job crafting. We discuss theoretical and practical implications.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Autonomy; Job crafting; Job design; Overqualification

Überqualifizierung im Kontext organisationaler Karrieren - Debus, Maike E.; Korner, Barbara (Gruppe. Interaktion. Organisation., 2018)
Überqualifizierung bezeichnet die Situation, in der Personen mehr Kenntnisse, Erfahrungen und Qualifikationen haben als für ihre Stelle benötigt werden. In den Industrieländern sind ca. 15 bis 20 % der Erwerbstätigen für ihre Stellen überqualifiziert. Es handelt sich somit um ein Phänomen, das Teil des organisationalen Alltags geworden ist. Im vorliegenden Beitrag gehen wir der Frage nach, welche Rolle Überqualifizierung für die Karriere- und Laufbahnentwicklung von Betroffenen spielt. Zuerst fassen wir die wesentlichen einstellungs-, befindens- und verhaltensbezogenen Korrelate von Überqualifizierung zusammen; danach zeigen wir auf, welche Zusammenhänge sich im Hinblick auf karrierebezogene Variablen ergeben. Basierend auf den teils konträren Befunden entwickeln wir ein theoretisches Rahmenmodell. In diesem Modell postulieren wir, dass proaktives Verhalten von Überqualifizierten eine Signalwirkung gegenüber organisationalen Entscheidungsträgern haben kann, wodurch karriereförderliche Entwicklungen angestoßen werden können. Abschließend diskutieren wir praktische Implikationen, die sich aus den berichteten Befunden und dem theoretischen Modell ergebe
CRIS-Team Scopus Importer:2020-04-02
Keywords: Career; Career success; Overqualification; Proactivity

Was, wenn mein Arbeitsplatz unsicher ist? Die Bedeutung von Arbeitsplatzunsicherheit für die berufliche Laufbahn und Karriere [What happens if my job is insecure? The impact of job insecurity in the context of careers] - Debus, Maike; König, Cornelius J. (Handbuch Karriere und Laufbahnmanagement, 2019)

Who will go the extra mile? Selecting organizational citizens with a personality-based structured job interview - Heimann, Anna Luca; Ingold, Pia V.; Debus, Maike; Kleinmann, Martin (Journal of Business and Psychology, 2020)
Employees’ organizational citizenship behaviors (OCB) are important drivers of organizational effectiveness. Yet, there exist no established tools for selecting employees with a propensity to engage in OCB. Given that personality traits describe typical behavioral tendencies and are established OCB predictors, we propose that personality assessment is a useful approach for selecting employees who are likely to exhibit OCB. To test this proposition, we developed a structured job interview measuring the Big Five traits and then compared this interview to a personality self-report measure to determine which method of personality assessment works best for selecting organizational citizens. Employees (N = 223) from various occupations participated in the structured job interview and completed the personality self-report in a simulated selection setting. We then obtained supervisor ratings of employees’ OCB. Results supported the assumption that structured job interviews can be specifically designed to assess the Big Five personality traits and, most importantly, to predict OCB. Interview ratings of specific personality traits differentially predicted different types of OCB (i.e., OCB-compliance, OCB-helping, and OCB-initiative) and explained incremental variance in OCB over and above personality self-reports and verbal cognitive ability. Taken together, these findings expand our knowledge about dispositional predictors of OCBs, personality assessment in selection, and the design of job interviews.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Organizational citizenship behavior; Personality traits; Personnel selection; Structured interviews